Testing carrier status in siblings of patients with cystic fibrosis. Issue 2 (February 1995) - Balfour-Lynn, I; Madge, S; Dinwiddie, R
Abstract : Altogether 114 parents of patients attending a cystic fibrosis clinic and 27 regional genetics units were surveyed for their views on whether healthy siblings should be tested for carrier status during childhood. Most parents wanted to know their child's carrier status and felt it was their right; almost all would tell the children if they were carriers. However, 37% of the units never tested siblings and 40% said the parents had no right to this knowledge. Furthermore, 60% would withhold the information from parents.